2012
DOI: 10.1590/s0102-86502012000900009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of unfractionated heparin and low molecular weight heparin on skin wound healing of rats

Abstract: PURPOSE:To compare the effects of unfractionated heparin (UH) and a low molecular weight heparin (LMWH) on skin wound healing of rats. METHODS: Forty eight male Sprague-Dawley rats underwent 8mm full thickness dorsal skin wounds and were randomly assigned to three equal groups. In experimental group A, heparin sodium was injected at a concentration of 1000U/kg. In experimental group B, enoxaparin was injected at a concentration of 1mg/kg. Physiologic saline (0.5ml) was administered to the control group. Inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…These properties of Hp further influence the cell proliferation, collagen restoration, epithelial cell differentiation, and signal transduction pathways in the wound. The function of Hp in the wound-healing process has been established in both cell line and animal studies . In several clinical studies, patients treated with heparin for burns and diabetic foot injury exhibited enhanced capillary circulation that led to reduced wound healing time .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties of Hp further influence the cell proliferation, collagen restoration, epithelial cell differentiation, and signal transduction pathways in the wound. The function of Hp in the wound-healing process has been established in both cell line and animal studies . In several clinical studies, patients treated with heparin for burns and diabetic foot injury exhibited enhanced capillary circulation that led to reduced wound healing time .…”
Section: Discussionmentioning
confidence: 99%
“…The function of Hp in the wound-healing process has been established in both cell line and animal studies. 37 In several clinical studies, patients treated with heparin for burns and diabetic foot injury exhibited enhanced capillary circulation that led to reduced wound healing time. 38 The wound healing properties of subcutaneously administered Hp was investigated on burn wounds of rats by Kus and Bienkiewicz, which results in a significant reduction in wound healing time.…”
Section: Discussionmentioning
confidence: 99%
“…Durmaz et al . [ 17 ] found that enoxaparin was better in the 7 th and 10 th days of wound healing than unfractionated heparin and the control group but did not compare with an oral anticoagulant agent. Although the findings of enoxaparin in the wound healing process differ in the literature, the difficulty of subcutaneous administration compared to oral drug intake restricts the use of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative phase of wound healing is significantly dependent on angiogenesis. Durmaz et al presented the positive effect of enoxaparin on skin wound healing in rats [20]. Norrby et al also presented a positive affect of dalteparin on VEGF-mediated angiogenesis.…”
Section: -Blood Estrogen Level Percentage Of Live Tissue and Angiogen...mentioning
confidence: 99%
“…Several authors have presented a negative effect of LMWH on angiogenesis [17][18][19]. On the other hand, the results of more works have shown a positive effect on wound healing and angiogenesis by LMWH application [20,21].…”
Section: Introductionmentioning
confidence: 99%